INFLUENCE OF TECHNOLOGICAL FACTORS OF THE KNITTING PROCESSON THE PARAMETERS OF THE STRUCTURE OF KNITTED MATERIAL COVER FOR THE STUMP - HALAVSKA, LIUDMYLA; DUDNYK, INNA; ARABULI, ARSENII; KOLCHYK, DENYS (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article highlights the results of studies on the influence of technological parameters of the knitting process on the structure parameters of tubular knitted materials intended to manufacture functional covers for stumps. The nature of the impact of knitting density, elastomeric yarn feed rate, and yarn laying report on the length of the yarn in the loop, thickness, surface density of knitwear, and the width of the semi-finished product tube is established. There is a global experience in manufacturing knitted stump covers with a compression effect. Such covers help to form the stump and relieve swelling during the rehabilitation phase before prosthetics. To create compression, an elastomeric thread is introduced into the structure of the knitted material. The tension of the elastomeric yarn and, accordingly, the level of compression of the cylindrical product is regulated during the knitting process by changing the speed of its feeding into the knitting zone. In the course of the work, prototypes of knitted materials with a 9.9-tex elastomeric (rubber) yarn with a double braid of 4.4-tex polyester textured yarn were made in the form of tuck stitch and float stitch with 1+1 and 1+3 reports. The warp of the fabric was made with a smooth plated weave, where cotton yarn with a linear density of 20 tex was used as the plating yarn and 4.4 tex textured polyamide yarn with a 2.2 tex elastane core as the warp. By the existing standardized methods, the structure parameters of the prototypes of knitted materials were determined, and the nature of the influence of knitting technological parameters on them was established. It has been found that the length of the thread in the loop is influenced by the set parameter of the vertical knitting density and the elastomeric yarn laying report. All other studied parameters of the loop structure and linear measurements of tubular knitted semi-finished products were sensitive to changes in the speed of elastomeric yarn feeding into the knitting zone, vertical knitting density, and the report of elastomeric (rubber) yarn laying in the soil structure of the knitted material. The correlation dependencies established during the research allow the design of knitted materials and tubular products for covers with specified parameters of the loop structure.